Penggunaan Agregat Sungai Walanae Kabupaten Wajo Sebagai Bahan Campuran Beton - Palimbong, Gita Yasty; Mara, Junus; Sanggaria, Olan Jujun (Universitas Kristen Indonesia Paulus, 2025)
Concrete is one type of construction material that is generally used for building projects, bridges, roads, and other buildings. The Walanae River in Wajo Regency is one of the rivers that produces materials in the form of aggregate used by the local community, but there is no certainty that the aggregate can be used as a concrete mixture. The formulation of the problem in this study is based on the background that has been described, namely, whether the characteristics of concrete using the aggregate of the Walanae River in Wajo Regency are qualified as concrete construction materials. To conduct laboratory tests on concrete samples using aggregate from the Walanae River, Wajo Regency to determine compressive strength, tensile strength, bending strength, and modulus of elasticity. Testing of 25 MPa and 30 MPa plan quality samples. The test pieces used were 42 samples, compressive strength 24 samples, tensile strength 6 samples, bending strength 6 samples, and elastic modulus 6 samples. Based on the results of the 28-day concrete testing research for 25 MPa quality, achieving the planned quality was 25,455 MPa. The results of the 28-day concrete test for 30 MPa quality did not reach the planned quality obtained 27,152 MPa. Aggregate from the Walanae River can be used effectively in the production of concrete of a quality suitable for the structure.